Assessment of Believes and Awareness about the Use of Natural Supplements for Weight management among Saudi Adults in Saudi Arabia. A Cross Sectional Descriptive Study - Samreen, Sana (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Natural supplements have gained significant attention due to their potential to aid in weight management. This study aimed to assess the beliefs and awareness about the use of natural supplements for weight loss among Saudi adults in Saudi Arabia. Methods: A cross-sectional, descriptive online survey was conducted among the public from March to April 2023 using Google Forms. The survey was divided into three themes and comprised 18 items that gathered information about the beliefs and awareness of respondents toward natural weight loss supplements. Data analysis was performed using the statistical package for social science version 27 (SPSS Inc., Armonk, New York, United States). Results: A total of 261 participants were included in the study. Among those, the majority of them were female, 253 (59.3%), and 75.1% had a university degree. About 28.7% (n = 75) were aged between 37 and 47 years. More than half (54%, n = 141) of the respondents were in good health, whereas 47.9% (n = 125) had a normal weight. In this study, 73.6% (n = 192) of the respondents never believed that using natural products to reduce weight. Furthermore, 25.7% (n = 67) of the participants sought medical assistance for the weight loss treatment. In addition, 33.7% (n = 88) of respondents were aware of the benefits of natural weightloss supplements. With regards to recommendation use of natural supplements, 6.5% (n = 17) of them reported health care professionals, followed by relatives and friends (17.6%, n = 46). In addition, 55.6% (n = 145) of the respondents revealed that social media and the internet, followed by health-care professionals (12.6%, n = 33), were the main sources of information for their natural supplements. Conclusion: The current findings revealed that 26.4% of adults believed the benefits of natural supplements for weight loss. The use of natural supplements is a fairly popular and traditional approach to managing weight. More awareness and education are required about the benefits and complications of natural supplements for weight loss or any other diseases that might be needed